Abemaciclib plus fulvestrant for the treatment of hormone receptor-positive/human epidermal growth factor receptor 2-negative breast cancer with cystic brain metastases: A case report and literature review - Chu, Zhaohui (Frontiers in Oncology, 2022)
Cystic brain metastases in patients with breast cancer are rare. They have a worse prognosis than solid brain metastases, and they are less sensitive to radiotherapy. We report a case of hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2−) metastatic breast cancer with cystic brain metastases. The patient underwent treatment with docetaxel combined with capecitabine for 5 months, followed by anastrozole maintenance therapy for 10 months and palbociclib combined with exemestane for 22 months. Cystic brain metastases emerged and bone metastases increased in number. A missense mutation in PIK3CA (exon 10, c.1633G>A [p.Glu545Lys]) was detected by whole-exome next-generation sequencing of peripheral blood samples. After whole-brain radiotherapy (40 Gy/20 fx) combined with 3 months of treatment with everolimus and fulvestrant, cystic brain metastases demonstrated partial remission (PR), but extracranial bone metastases continued to increase in number. Thus, the patient underwent fourth-line treatment with abemaciclib (100 mg bid) combined with fulvestrant (500 mg). Three months later, cystic brain metastases significantly demonstrated PR and extracranial bone metastases were stable. Until present, the patient has above 9 months of progression-free survival time without obvious adverse effects. This is the first report of abemaciclib combined with fulvestrant in the treatment of cystic brain metastases in a patient with HR+/HER2− breast cancer.